Penanganan Obat Look Alike Sound Alike (LASA) dalam Praktik Kefarmasian: Tinjauan Literatur Naratif: PENANGANAN OBAT LOOK-ALIKE SOUND-ALIKE (LASA) DALAM PRAKTIK KEFARMASIAN: TINJAUAN LITERATUR NARATIF - Muhammad Zaini; Nazhipah Isnani; Siti Nur Hikmah; Muliyani Muliyani (Politeknik Unggulan Kalimantan, 2025)
Medication errors remain a sndaignificant challenge in efforts to improve patient safety, one of which is triggered by the use of Look Alike Sound Alike (LASA) medications. LASA drugs share similarities in naming, pronunciation, or packaging appearance, thereby increasing the risk of errors during prescribing, preparation, and administration stages. This article aims to review the literature addressing the concept, impact, and management strategies of LASA medications in pharmacy practice from a pharmaceutical management perspective. The research method employed was a narrative literature review of scientific articles published within the last five years and sourced from the Scopus and PubMed databases. The findings indicate that optimal management of LASA medications requires a systematic approach through risk management policies, implementation of standard operating procedures, utilization of health information technology, and strengthening the role of pharmacists within the healthcare system. However, empirical studies examining the effectiveness of LASA policy implementation in healthcare facilities in Indonesia remain limited. Therefore, the development of contextual and sustainable LASA management models is needed to support the enhancement of patient safety.